Research of the sphere of application of a flexible method of implementation of train movement graphics - Svetashev A.A.; Soliev A.U. (Научно-технический вестник Брянского государственного университета)
The purpose of this article is to justify the use of a flexible method for implementing the train schedule at the sorting stations and the parameters characterizing it, as well as the dependencies that determine these parameters and the costs of car-hours for the accumulation of wagons. Results: The article gives a detailed analysis of the process of accumulation of wagons for the composition in the sorting park of the station with a flexible method of implementing the schedule. Formulas are proposed for determining the average daily expenses of car-hours for accumulation and the accumulation parameter of the compositions. The calculation is shown and the average statistical values of the investigated quantities are determined. Practical significance: is the detailed consideration of the process of accumulation of cars with the magnitude of deviation from the maximum norm, the composition in the smaller direction and its effect on the costs of car-hours for the accumulation of wagons.